Efektivitas dan Benefit Incidence Analysis terhadap Kebijakan BOS pada SMP Negeri di Kecamatan Bonang - Maf'alul Izzah; Evi Yulia Purwanti (Diponegoro Journal of Economics, 2022)
The decline in the quality of the education sector prompted the government to intervene. To educate the nation in accordance with the mandate of the law, the government provides assistance in the form of school operational assistance. The purpose of this study was to determine the effectiveness and accuracy of the distribution of benefits from the BOS policy in public junior high schools in Bonang District. This study employs a quantitative descriptive method with four relevant indicators to assess effectiveness and uses the Benefit Incident Analysis (BIA) method to evaluate the distribution of benefits from the policy. Based on the results of the research conducted in public junior high schools in Bonang District, the program cannot be deemed effective. While the Flexibility and Accountability Indicators are considered effective, the Transparency Indicator remains ineffective. The distribution of benefits from the program is minimal, at only 9%, leading to the conclusion that the policy can be classified as regressive.